Porphyromonas gingivalis LPS stimulates the expression of LPS-binding protein in human oral keratinocytes in vitro. Issue 1 (February 2013) - Ding, Pei-Hui; Wang, Cun-Yu; Darveau, Richard P; Jin, Lijian
LPS-binding protein (LBP) functions as a crucial molecule in innate immune responses to bacterial challenge. Our study has shown the expression of LBP in human gingiva and its significant association with periodontal health and disease. Porphyromonas gingivalis is a key pathogen of periodontal disease. P. gingivalis LPS as a main virulence factor is strongly involved in periodontal pathogenesis and it displays a significant lipid A structural heterogeneity. Currently, it remains unknown whether, and to what extent, the lipid A structural heterogeneity of P. gingivalis LPS affects LBP expression. The present study investigated the expression profile of LBP in human oral keratinocytes (HOKs) stimulated by two isoforms of P. gingivalis LPS [tetra- (LPS1435/1449 ) and penta-acylated (LPS1690 )] and Escherichia coli LPS, and the involvement of TLRs in LBP expression. The results showed that the expression of LBP mRNA and peptide was significantly up-regulated by P. gingivalis LPS1690 and E. coli LPS, while P. gingivalis LPS1435/1449 did not affect LBP expression. Blocking assay and siRNA gene silencing revealed that P. gingivalis LPS1690 -induced LBP expression was through both TLR2 and TLR4. This in vitro study demonstrates that P. gingivalis LPS with a lipid A structural heterogeneity differentially modulates LBP expression in HOKs.